2000
DOI: 10.1074/jbc.m001426200
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and Supramolecular Organization of EMILIN

Abstract: The primary structure of human Elastin microfibril interface-located protein (EMILIN), an elastic fiber-associated glycoprotein, consists of a globular C1q domain (gC1q) at the C terminus, a short collagenous stalk, a long region with a high potential for forming coiled-coil ␣ helices, and a cysteine-rich N-terminal sequence. It is not known whether the EMILIN gC1q domain is involved in the assembly process and in the supramolecular organization as shown for the similar domain of collagen X. By employing the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 51 publications
(54 reference statements)
3
50
0
Order By: Relevance
“…Based on the homotrimeric model of ACRP30 gC1q crystal structure (10), it was supposed that the EMILIN1 gC1q domain could also trimerize via several hydrophobic residues. This was confirmed, first by biochemical (3,7) and later by preliminary structural evidence (14).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Based on the homotrimeric model of ACRP30 gC1q crystal structure (10), it was supposed that the EMILIN1 gC1q domain could also trimerize via several hydrophobic residues. This was confirmed, first by biochemical (3,7) and later by preliminary structural evidence (14).…”
supporting
confidence: 58%
“…Thus, EMILIN1 favorably located at the subendothelium of blood vessels is a new specific antagonist of tumor growth factor-␤, and the function of this constituent of elastic tissues is linked to the pathogenesis of hypertension. The C-terminal gC1q domain is involved in the oligomerization of EMILIN1 (7), in cell adhesion and migration via interaction with the ␣4␤1 integrin (8), and in trophoblast invasion (9).…”
mentioning
confidence: 99%
“…Exploiting the yeast two-hybrid system with EMI-LIN-1 indicates that trimerization is initiated by the C1q-like domain followed by a subsequent quarternary assembly mediated by intermolecular disulfide bridges, which was further supported by the fact that a deletion mutant of EMILIN-1, lacking the C1q-like domain, was incapable in multimer formation (21). Our analysis shows that the C-terminal portion of EndoGlyx-1 p125/140 consists of an C1q-like domain homologous to EMILIN-1 and multimerin, with 26 and 32% amino acid sequence identity, respectively, which is in accordance with the oligomerization of the different EndoGlyx-1 subunits mediated by intermolecular disulfide bridges.…”
Section: Identification Of Endoglyx-1 48591mentioning
confidence: 82%
“…Additionally, a significant level of conservation was found for the C-terminal C1q-like domain, between amino acids 818 and 949, with 26% sequence identity with the respective region in the human EMILIN-1 precursor protein and 32% sequence identity with the human multimerin precursor protein (Fig. 4B), indicating a shared functional feature provided by this segment, such as the formation of homomultimers, which was demonstrated for several members of the TNF/C1q superfamily (21). Additional sequence analysis details can be viewed at mendel.imp.univie.ac.at.SEQUENCES/endoglyx/.…”
Section: Vascular Expression Of Endoglyx-1-mentioning
confidence: 91%
“…Early studies on the procollagen precursors of the fibrillar collagens (types I-III, V, and XI) (6) showed that the C-propeptide regions are necessary to direct correct chain association, which is followed by zipper-like folding of the triple helix in the C-to N-terminal direction (7). This concept was subsequently extended to basement membrane collagen type IV (8 -10), microfibril-forming collagen VI (11,12), members of the C1q family (13) including collagens VIII and X (14 -17) and the emilins (18), and the FACITs 1 (19 -21).…”
mentioning
confidence: 99%